2011
DOI: 10.1002/chp.20100
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Tobacco Cessation Skills to Uruguayan Physicians Using Information and Communication Technologies

Abstract: The need to train physicians on tobacco cessation skills can be addressed via ICTs and educational activities that include participant interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Our findings are consistent with the previous research which showed that the combination of computer-assisted instruction and traditional classroom lecture yielded a significantly greater improvement in knowledge achievement of nursing students than when either strategy is used alone in the context of congenital heart disease [16]. Similarly, Llambí et al [19] reported that Uruguayan physicians who completed a blended-learning course on tobacco cessation achieved better test scores than those who attended pure online course. Furthermore, our quantitative results in this study also showed that blended learners expressed more positive ratings about goal achievement than online learners.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with the previous research which showed that the combination of computer-assisted instruction and traditional classroom lecture yielded a significantly greater improvement in knowledge achievement of nursing students than when either strategy is used alone in the context of congenital heart disease [16]. Similarly, Llambí et al [19] reported that Uruguayan physicians who completed a blended-learning course on tobacco cessation achieved better test scores than those who attended pure online course. Furthermore, our quantitative results in this study also showed that blended learners expressed more positive ratings about goal achievement than online learners.…”
Section: Discussionsupporting
confidence: 92%
“…Cook et al’s [15] systematic review reported that Internet-based learning had more positive effects when compared with no intervention in health professions, but more comparisons of different Internet-based interventions need to be conducted. To our knowledge, there is limited evidence on the effects of blended learning in comparison with pure e-learning [16-19]. In another systematic review in 2016, Liu et al [20] showed that blended learning is more effective or at least as effective as pure e-learning or pure traditional face-to-face learning among health professions and suggested that the more evaluation studies of blended learning, especially with e-learning should be conducted in future research.…”
Section: Introductionmentioning
confidence: 99%
“…Less than 15% of generalists compared with 35%–45% of specialists who participated in online courses completed all course requirements and received a diploma . Similar differences between specialist and generalist participation have been observed in national and international CME programs in 20 countries in Latin America …”
Section: Introductionsupporting
confidence: 63%
“…Specialists in Latin America, for example, tend to have higher rates of attendance, participate more actively in discussions, and feel more comfortable sharing personal practice experiences with peers and faculty. Specialists are more likely to complete course requirements . One of the authors (AM) and colleagues report that less than 10% of the general practitioners and family physicians of the invited audience in the Latin American region attended CME courses that were free and designed to meet their practice needs .…”
Section: Introductionmentioning
confidence: 99%
“…Much in-depth research has been done on individual cases of BL worldwide (Boitshwarelo, 2009;Hoic-Bozic, Mornar, & Boticki, 2009;Llambi et al, 2011). Also a few examples of research have concentrated on a larger region.…”
Section: Review Of Related Literaturementioning
confidence: 99%